2021
DOI: 10.1161/cir.0000000000001018
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Promotion of a Healthy Lifestyle in Clinical Settings: Pillars of Ideal Cardiovascular Health: A Science Advisory From the American Heart Association

Abstract: Engagement in healthy lifestyle behaviors is suboptimal. The vast majority of the US population does not meet current recommendations. A healthy lifestyle is defined by consuming a healthy dietary pattern, engaging in regular physical activity, avoiding exposure to tobacco products, habitually attaining adequate amounts of sleep, and managing stress levels. For all these health behaviors there are well-established guidelines; however, promotion in clinical settings can be challenging. It is critical to overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 120 publications
0
31
0
4
Order By: Relevance
“…Kris-Etherton et al 25 publicaron el 2021 un documento en el que presentan algunas estrategias para que el personal médico y demás profesionales de la salud las usen en el asesoramiento sobre cambios de comportamiento relacionados con el estilo de vida en todos los niveles de riesgo de enfermedad cardiovascular (prevención primaria y secundaria). Este documento se basa en el uso del modelo 5A (asess, advise, agree, assist and arrange), que originalmente fue desarrollado para la cesación del consumo de tabaco, pero que se ha identificado como un marco unificador para el asesoramiento conductual en la atención primaria y de servicios preventivos.…”
Section: Discussionunclassified
“…Kris-Etherton et al 25 publicaron el 2021 un documento en el que presentan algunas estrategias para que el personal médico y demás profesionales de la salud las usen en el asesoramiento sobre cambios de comportamiento relacionados con el estilo de vida en todos los niveles de riesgo de enfermedad cardiovascular (prevención primaria y secundaria). Este documento se basa en el uso del modelo 5A (asess, advise, agree, assist and arrange), que originalmente fue desarrollado para la cesación del consumo de tabaco, pero que se ha identificado como un marco unificador para el asesoramiento conductual en la atención primaria y de servicios preventivos.…”
Section: Discussionunclassified
“…E-cigarette use has increased over the last decade primarily in adolescents (12–19 years of age) [ 59 ]. In 2019, the National Youth and Tobacco Survey found that about 8 million (53.3%) high school students and 2.9 million (24.3%) middle school students reported ever using tobacco products of which e-cigarettes were the most common (35.0%) [ 9 •]. Although the long-term effects are not yet confirmed, the metabolic damage seen in e-cigarette users aligns with those seen in smokers.…”
Section: Avoid Tobacco Exposurementioning
confidence: 99%
“…Consequently, there is a pressing need to identify strategies that promote the adoption of healthy lifestyle behaviors. Using the 5A model (assess, advise, agree, assist, and arrange) for behavior change, two recent AHA Scientific Statements have provided the framework for counseling on behavior change to achieve healthy lifestyle behaviors [ 8 •, 9 •].…”
Section: Introductionmentioning
confidence: 99%
“…They increase the individual level of self-care, happiness, and self-actualization, thus leading the way to optimal health and wellbeing [ 17 ]. Evidence shows that health behavior interventions are important to promoting healthy eating habits and regular physical activities, which are essential to reducing the risk of developing chronic health conditions such as diabetes, cardiovascular diseases (CVDs), hypertension, and obesity [ 16 , 18 ]. A study by Devaraj et al documented that 94% of the participants made healthier food choices due to the influences of healthy diet intervention, and also improved their physical activity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%